Causal Opacity or Causal Translucence? Magic, Causal Heuristics and the “Ritual Stance” - Larson, Jennifer (Journal of Cognitive Historiography, 2024)
According to longstanding interpretations in the social and cognitive sciences, rituals are said to be characterized by arbitrary action and the lack of a causal connection between action and desired outcome. The observer who assigns a physical-causal connection has taken the instrumental stance, while one who accepts a group convention is said to take the ritual stance. I argue that in religious rituals at least, including those with magical elements, the gap is bridged and causal intuitions are present, if limited. For example, we rely on a mental heuristic called Representativeness in order to make many causal judgments, and Representativeness tells us that effects usually resemble their causes. This heuristic, studied by Daniel Kahnemann and Amos Tversky, corresponds to J. G. Frazer’s so-called “Law of Similarity” in magic. Representativeness and other forms of magical thinking appear to yield weaker causal inferences than our intuitions about physical processes or the agency of other people. Accordingly, religious rituals are often employed in situations where a goal cannot be achieved in more obvious ways, but some lesser intuition of causal efficacy can still be generated. Illustrative examples are drawn from ancient Greek rituals of offering, oath-taking, and purification.